Developing New Antimicrobial Therapies: Are Synergistic Combinations of Plant Extracts/Compounds with Conventional Antibiotics the Solution? - Cheesman, Matthew J.; Ilanko, Aishwarya; Blonk, Baxter; Cock, Ian E. (Pharmacognosy Reviews)
The discovery of penicillin nearly 90 years ago revolutionized the treatment of bacterial disease. Since that time, numerous other antibiotics have been discovered from bacteria and fungi, or developed by chemical synthesis and have become effective chemotherapeutic options. However, the misuse of antibiotics has lessened the efficacy of many commonly used antibiotics. The emergence of resistant strains of bacteria has seriously limited our ability to treat bacterial illness, and new antibiotics are desperately needed. Since the discovery of penicillin, most antibiotic development has focused on the discovery of new antibiotics derived from microbial sources, or on the synthesis of new compounds using existing antibiotic scaffolds to the detriment of other lines of discovery. Both of these methods have been fruitful. However, for a number of reasons discussed in this review, these strategies are unlikely to provide the same wealth of new antibiotics in the future. Indeed, the number of newly developed antibiotics has decreased dramatically in recent years. Instead, a reexamination of traditional medicines has become more common and has already provided several new antibiotics. Traditional medicine plants are likely to provide further new antibiotics in the future. However, the use of plant extracts or pure natural compounds in combination with conventional antibiotics may hold greater promise for rapidly providing affordable treatment options. Indeed, some combinational antibiotic therapies are already clinically available. This study reviews the recent literature on combinational antibiotic therapies to highlight their potential and to guide future research in this field.
Keywords: β‑lactamase; clavulanic acid; efflux pump inhibitors; multi‑drug resistance; superbugs; synergy